A randomised controlled trial to evaluate the impact of a human rights based approach to dementia care in inpatient ward and care home settings - Peter Kinderman; Sarah Butchard; Ashley J Bruen; Abbie Wall; Nia Goulden; Zoe Hoare; Carys Jones; Rhiannon Edwards (National Institute for Health Research, 2018)
Background: Although it is widely recognised that adopting a person-centred approach is beneficial in the care of people living with dementia, a gap remains between the rhetoric and the reality of quality care. Some widely adopted care practices can result in the personhood of this group being threatened and their human rights being undermined. Objectives: To evaluate the impact of applying a human rights based approach in dementia inpatient wards and care homes on the quality of care delivered and the well-being of the person living with dementia. Design: A cluster randomised design was employed to compare the impact of implementing a human rights based approach intervention (i.e. training, applying the 'Getting It Right' assessment tool and receiving booster sessions) at 10 intervention sites with 10 control sites. Setting: Eight NHS dementia inpatient wards and 12 care homes in the north-west of England. Participants: People living with dementia who were residing on dementia inpatient wards or in care homes, and staff working at these sites. The aim was to recruit 280 people living with dementia. Interventions: A sample of staff (an average of 8.9 per site) at each of the sites was trained in a human rights based approach to care, including the application of the 'Getting It Right' assessment tool. The tool was then introduced at the site and monthly booster sessions were delivered. Main outcome measures: The primary outcome measure used in the research was the Quality of Life in Alzheimer's Disease scale to assess the subjective well-being of the person with dementia. Secondary outcome measures included measures of the quality of care provided (dementia care mapping) and direct measures of the effectiveness of the training in increasing knowledge of and attitudes towards human rights. The study also included an economic evaluation utilising the EuroQol-5 Dimensions, three-level version, and the Adult Social Care Outcomes Toolkit measure. Results: The study recruited 439 people living with dementia: 213 to the intervention arm and 226 to the control arm. Primary outcome data were analysed using a linear mixed model. There were no significant differences found in the reported quality of life of residents between the control and intervention groups after the intervention [F(1,16.51) = 3.63; p = 0.074]. The mean difference between the groups was 1.48 (95% confidence interval -7.86 to 10.82). Conclusions: Despite the fact that the training increased staff knowledge of and positive attitudes towards human rights, and although there were some changes in staff decision-making strategies in clinical situations, there was no change in the quality of care provided or in the reported well-being of people living with dementia in these settings. This led to questions about the efficacy of training in bringing about cultural change and improving care practices. Limitations: There was limited uptake of the training and booster sessions that were integral to the intervention. Future work: Future work could usefully focus on understanding the difficulty in translating change in attitude and knowledge into behaviour. Trial registration: Current Controlled Trials ISRCTN94553028. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 6, No. 13. See the NIHR Journals Library website for further project information.